Quantum critical behavior in the asymptotic limit of high disorder in the medium entropy alloy NiCoCr0.8 - Brian C. Sales (Nature Portfolio, 2017)
Quantum criticality: metallic ferromagnetic systems A family of metallic solid solutions—alloys characterized by extreme chemical disorder—are found to exhibit quantum critical behaviour. Few metallic systems are known to show this type of phase transition, and research on the topic has mainly focused on low dimensional magnetic insulators. Our current understanding of this phenomenon is consequently very limited. Now, Brian C. Sales and colleagues at USA’s Oak Ridge National Laboratory, and collaborators from National Institute of Standards and Technology and University of Maryland, report quantum criticality as a function of temperature and magnetic field in NiCoCrx single crystals, which are metallic ferromagnetic solid solutions. Over two hundred ternary solid solutions have been predicted to exist, and they may therefore represent the perfect platform for studying these quantum phase transitions.